An evaluation of different Cripto‐1 antibodies and their variable results - Gudbergsson, Johann Mar; Duroux, Meg (Journal of cellular biochemistry, 2020)
Cripto‐1 is a protein expressed during embryonal development and has been linked to several malignant processes in cancer. Since the discovery of cripto‐1 in the late 1980s, it has become a subject of biomarker investigation in several types of cancer which in many cases relies on immunolocalization of cripto‐1 using antibodies. Investigating cripto‐1 expression and localization in primary glioblastoma cells, we discovered nonspecific binding of cripto‐1 antibody to the extracellular matrix Geltrex. A panel of four cripto‐1 antibodies was investigated with respect to their binding to the Geltrex matrix and to the cripto‐1 positive control cells NTERA2. The cripto‐1 expression was varied for the different antibodies with respect to cellular localization and fixation methods. To further elaborate on these findings, we present a systematic review of cripto‐1 antibodies found in the literature and highlight some possible cross reactants with data on sequence alignments and structural comparison of EGF domains. Cripto‐1 has become a popular biomarker for cancer prognosis, however, many studies utilize poorly characterized antibodies. We provide evidence for differential binding patterns of these antibodies in fluorescence microscopy and suggest a potential pitfall in cripto‐1 antibody‐based studies.